Pelatihan Penyusunan Asesmen Diagnostik dalam Kurikulum Merdeka bagi Guru di MTs dan MA Sekolah Cinta Ilmu - Ahmad Mukhibin; Husnul Khatimah Rusyid; Ahmad Lutfi; Syifa Mardliyah; Jarnawi Afgani Dahlan; Al Jupri (Jurnal Surya Masyarakat, 2024)
Merdeka curriculum was developed by the Government in order to improve the quality of education in Indonesia. Merdeka Curriculum, introduced by the Ministry of Education, Culture, Research and Technology (Kemendikbud Ristek), is a new curriculum that allows schools to adapt learning to the needs and characteristics of students. However, in its implementation, teachers experience several obstacles in implementing the independent curriculum, one of which is in designing assessments and evaluations. Teachers have difficulty in managing classroom conditions due to the lack of clarity in diagnostic assessments. This research aims to provide training in preparing diagnostic assessments to determine students' initial abilities before learning. The method used in this community service is Participatory Action Research (PAR). The subjects in this study were MTs and MA teachers at Cinta Ilmu School, totaling 18 people. Based on the data obtained during the training, the teachers felt enthusiastic and satisfied with the presentation of material that was in accordance with the needs and professional presenters so that the material provided could be easily understood by the participants. It is indicated by the average score index of overall participant satisfaction reaching 3.54, which is in the very satisfying category. While the satisfaction index in the reliability aspect reached a score of 3.7, the tangible evidence aspect reached 3.5, the responsiveness aspect reached 3.4, the guarantee aspect reached 3.5, and the service aspect reached 3.6.